Defending checks and balances in EU member states : taking stock of Europe's actions - Bogdandy, Armin von, 1960-; Bogdanowicz, Piotr; Canor, Iris; Grabenwarter, Christoph; Taborowski, Maciej; Schmidt, Matthias (Springer, 2021)
This open access book deals with Article 7 TEU measures, court proceedings, financial sanctions and the EU Rule of Law Framework to protect EU values with a particular focus on checks and balances in EU Member States. It analyses substantive standards, powers, procedures as well as the consequences and implications of the various instruments. It combines the analysis of the European level, be it the EU or the Council of Europe, with that of the national level, in particular in Hungary and Poland. The LM judgment of the European Court of Justice is made subject to detailed scrutiny.
Keywords: Separation of powers -- European Union countries.; European Union countries -- Politics and government.; Séparation des pouvoirs -- Pays de l'Union européenne.; Politics and government; Separation of powers; European Union countries; European Fundamental Rights and Freedoms; Treaty of the European Union; Court of Justice of the European Union; Member States; CJEU; Democracy; Rule of Law; EU Values; Constitutional Crisis; Open access; Public international law: human rights; Electronic books.